Development and validation of LC–QTOF–MS/MS method for the identification and determination of low levels of a genotoxic impurity, 4, 6‐dichloro‐5‐nitro‐2‐(propylthio)pyrimidine in ticagrelor API. (26th January 2022) - Moorthy, Manchuri Krishna; Ali, Shaik Mahammad; Reddy, Gopireddy Venkata Subba
Abstract: The foremost objective of the present study was to develop and validate a new LC–QTOF–MS/MS method for the identification and quantitative determination of 4, 6‐dichloro‐5‐nitro‐2‐(propylthio)pyrimidine (DPP) genotoxic impurity through the derivatization process in ticagrelor active pharmaceutical ingredient (API). Owing to the low response of DPP at the specification level, DPP was converted to 4, 6‐dibenzylamino‐5‐nitro‐2‐(propylthio)pyrimidine (DPP derivative) by addition of benzyl amine, then analyzed using mass spectrometry with a time‐of‐flight analyzer, and good separation was accomplished under the experimental conditions described. The effective separation of DPP derivative was achieved using an Acquity UPLC BEH C18 reverse‐phase column (100 × 4.6 mm × 1.7 μm) with an isocratic program with mobile phase A as 0.1% formic acid in milli Q water and mobile phase B as acetonitrile in the ratio of 20:80 v/v. The flow rate was maintained as 0.4 ml/min, the injection volume was 2 μl, the autosampler temperature was 5°C, the column oven temperature was ambient and the run time was 6.0 min. The diluent used was 0.2% benzyl amine in water and acetonitrile in the ratio of 30:70 v/v. The retention time of the DPP derivative was 2.87 min. The limit of detection and limit of quantification were 0.03 and 0.08 ppm, respectively. The DPP derivative was linear from 1.68 to 12.78 ppm with R 2 of 0.9958. Thus, the developed method is valid for the identification and quantitative determination of DPP derivative in ticagrelor API.